2020
DOI: 10.1111/add.15009
|View full text |Cite
|
Sign up to set email alerts
|

Associations between neighborhood‐level factors and opioid‐related mortality: A multi‐level analysis using death certificate data

Abstract: Aim To identify associations between opioid‐related mortality and neighborhood‐level risk factors. Design Cross‐sectional study. Setting Massachusetts, USA. Participants Using 2011–14 Massachusetts death certificate data, we identified opioid‐related (n = 3089) and non‐opioid‐related premature deaths (n = 8729). Measurements The independent variables consisted of four sets of neighborhood‐level factors: (1) psychosocial, (2) economic, (3) built environment and (4) health‐related. At the individual level we inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 54 publications
0
10
0
1
Order By: Relevance
“…These systems were included within access to resources due to their ability to serve and engage the community (Joudrey et al, 2019 ). Specifically, FQHC's serve medically underserved areas, provide a wide range of services, including counseling and medication-assisted treatment, and have been shown to be associated with opioid-related mortality (Haley et al, 2019 ; Flores et al, 2020 ). Access to pharmacies with a standing order for naloxone (from the IDPH registry), “drug use disorder treatment programs” (as defined by methadone outpatient treatment clinics), buprenorphine-waivered physicians with records of prescribing in the Illinois Prescription Monitoring Program, and naltrexone providers (sourced from the Substance Abuse and Mental Health Services Administration 2018 dataset), and federally qualified health centers (from study collection) were available as locations at the address level, and subsequently geocoded and converted to spatial data points.…”
Section: Methodsmentioning
confidence: 99%
“…These systems were included within access to resources due to their ability to serve and engage the community (Joudrey et al, 2019 ). Specifically, FQHC's serve medically underserved areas, provide a wide range of services, including counseling and medication-assisted treatment, and have been shown to be associated with opioid-related mortality (Haley et al, 2019 ; Flores et al, 2020 ). Access to pharmacies with a standing order for naloxone (from the IDPH registry), “drug use disorder treatment programs” (as defined by methadone outpatient treatment clinics), buprenorphine-waivered physicians with records of prescribing in the Illinois Prescription Monitoring Program, and naltrexone providers (sourced from the Substance Abuse and Mental Health Services Administration 2018 dataset), and federally qualified health centers (from study collection) were available as locations at the address level, and subsequently geocoded and converted to spatial data points.…”
Section: Methodsmentioning
confidence: 99%
“…Another more limited line of research has focused on the components of the social, economic, and health environment that are associated with the risk of opioid-related mortality (Monnat 2018; Flores et al 2020; Wunsch et al 2009; Ruhm 2017; Keyes et al 2014; West et al 2015; Lippold et al 2019; Lippold and Ali 2020; McClellan 2019). These studies disagree on the direction of the association of food insecurity and opioid-related deaths.…”
Section: The Connection Between Food Insecurity and The Opioid Crisismentioning
confidence: 99%
“…One study (Langabeer et al 2020) explored the correlation of seventeen county-level characteristics with population-weighted opioid-related mortality averaged over 2016 and 2017 and found that levels of county food insecurity were negatively correlated with opioid-related mortality. Another study (Flores et al 2020) used block group and county-level data from Massachusetts and 2011 to 2014 pooled mortality related deaths to estimate multilevel models. They found that the county food insecurity rate was positively associated with opioid-related mortality.…”
Section: The Connection Between Food Insecurity and The Opioid Crisismentioning
confidence: 99%
See 1 more Smart Citation
“…The coronavirus pandemic is an additional major burden to communities already struggling to stem the ongoing opioid crisis (Alexander et al, 2020; Becker & Fiellin, 2020; Volkow, 2020) as well as other health disparities. Social determinants of health such as greater poverty, food insecurity, and fewer per‐capita social associations (Flores et al, 2020) COVID‐19 further exacerbate racial and income inequalities in opioid mortalities.…”
Section: Higher Underlying Infection Risk and Worse Infection‐relatedmentioning
confidence: 99%